VALIDITAS LEMBAR KERJA MAHASISWA UNTUK MENINGKATKAN LITERASI SAINS PADA MATA KULIAH FISIKA BIOLOGI - Dewantara, Dewi; Mahtari, Saiyidah; Haryandi, Surya (Universitas Hamzanwadi, 2020)
The use of student's worksheets in biology physics lectures will contribute to optimizing the achievement of learning objectives in conveying material from lecturers to students and the achievement of scientific literacy skills to students. This article aims to describe the validation of student worksheets in Biology Physics courses to improve student scientific literacy. Development research was carried out in the Lambung Mangkurat University Physics Education Study Program 2019/2020. Validation is one of the processes at the part of the development stage. The validity of student's worksheets is measured using a validation sheet and then determined based on validation by experts which are stated as Valid or invalid. If valid, it will be categorized again as very good, good, enough, less, and not very good. The conclusion of this article is the Student Worksheet for increasing scientific literacy in Physics Biology courses is valid in both categories. Thus this Worksheet can be implemented for further testing at the dissemination stage.